KF1601, a dual inhibitor of BCR::ABL1 and FLT3, overcomes drug resistance in FLT3+ blast phase chronic myeloid leukemia - Kwon, Hyun-Jin; Shin, Ji Eun; Khan, Amir; Park, So Yeon; Kim, Jiyoung; Lee, Jee-Young; Lee, Doohyun; Lee, Seungyeon; Im, Chun Young; Moon, Heegyum; Han, Ye Ri; Tamai, Minori; et al. (BioMed Central, 2025)
Blast phase chronic myeloid leukemia (BP-CML) poses significant clinical challenges due to its drug resistance, resulting from BCR::ABL1-dependent mutations and BCR::ABL1-independent pathways. Previously, we reported that FLT3 pathway is activated in similar to 50% of BP-CML cases, indicating a potential avenue for therapeutic intervention via dual inhibition of BCR::ABL1 and FLT3. Here, we aimed to evaluate the efficacy of KF1601, a dual inhibitor of BCR::ABL1 and FLT3, in overcoming drug resistance in BP-CML while also comparing its thrombo-inflammatory responses with those of ponatinib, known to have severe cardiovascular adverse events in human. Our findings revealed that KF1601 effectively inhibited of BCR::ABL1 signaling pathway, even in the presence of the T315I mutation. KF1601 achieved complete tumor regression in K562 xenograft mouse models, and prolonged survival significantly in orthotopic mouse models. Furthermore, KF1601 effectively inhibited the FLT3 signaling pathway in imatinib-resistant K562 cells expressing FLT3 and TAZ, suppressing cell proliferation through dual inhibition of BCR::ABL1 and FLT3. These findings were corroborated using drug-resistant BP-CML cells from patients. In assessing thrombo-inflammatory responses using a murine thrombosis model, ponatinib induced severe responses, leading to carotid artery occlusion and extensive vessel wall damage. In contrast, in mice treated with KF1601, carotid arteries remained unoccluded, with vessel walls preserved intact. In summary, KF1601 demonstrated promising preclinical efficacy in overcoming resistance mechanisms, including the BCR::ABL1(T315I) mutation, while also addressing FLT3 signaling implicated in BP-CML progression. Unlike existing therapies such as ponatinib, KF1601 offers a favorable safety profile, potentially minimizing the risk of life-threatening adverse effects.